2021
DOI: 10.1152/japplphysiol.00543.2021
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise with blood flow restriction causes local and systemic hypoalgesia and increases circulating opioid and endocannabinoid levels

Abstract: Aim: This study examined the effect of aerobic exercise with and without blood flow restriction on exercise-induced hypoalgesia and endogenous opioid and endocannabinoid systems. Methodology: In a randomised crossover design, pain-free individuals performed 20 min of cycling in four experimental trials: 1) Low intensity aerobic exercise (LI-AE) at 40% V̇O2max; 2) LI-AE with low pressure BFR (BFR40); 3) LI-AE with high pressure BFR (BFR80); and 4) High intensity aerobic exercise (HI-AE) 70% V̇O2max. Pressure pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…IPC-induced hypoalgesia may be governed by endogenous substances that have antinociceptive effects on pain pathways. Metabolic mediators including adenosine, bradykinin, opioids, and endocannabinoids–all of which are involved in pain signalling during exercise ( Sgherza et al, 2002 ; Murase et al, 2010 ; Aguiar et al, 2020 ; Hughes and Patterson, 2020 ; Hughes et al, 2021 )—have been purported to contribute to the protective response to RIPC ( Lee et al, 1996 ; Tomai et al, 1999 ; Cohen et al, 2000 ; Schoemaker and van Heijningen, 2000 ; Dickson et al, 2002 ; Patel et al, 2002 ; Hajrasouliha et al, 2008 ). Furthermore, the endogenous release of some of these autacoids is thought to modulate the stimulation and signalling of group III/IV afferents ( Amann et al, 2009 , Amann et al, 2011 ; Bouffard et al, 2021 ).…”
Section: Effect Of Ipc On Neurological and Perceptual Responses To Ex...mentioning
confidence: 99%
See 1 more Smart Citation
“…IPC-induced hypoalgesia may be governed by endogenous substances that have antinociceptive effects on pain pathways. Metabolic mediators including adenosine, bradykinin, opioids, and endocannabinoids–all of which are involved in pain signalling during exercise ( Sgherza et al, 2002 ; Murase et al, 2010 ; Aguiar et al, 2020 ; Hughes and Patterson, 2020 ; Hughes et al, 2021 )—have been purported to contribute to the protective response to RIPC ( Lee et al, 1996 ; Tomai et al, 1999 ; Cohen et al, 2000 ; Schoemaker and van Heijningen, 2000 ; Dickson et al, 2002 ; Patel et al, 2002 ; Hajrasouliha et al, 2008 ). Furthermore, the endogenous release of some of these autacoids is thought to modulate the stimulation and signalling of group III/IV afferents ( Amann et al, 2009 , Amann et al, 2011 ; Bouffard et al, 2021 ).…”
Section: Effect Of Ipc On Neurological and Perceptual Responses To Ex...mentioning
confidence: 99%
“…Indeed, activation of opioid and endocannabinoid receptors in the central and peripheral sites of the pain pathway such as the spine and peripheral nerves can modulate ascending and descending pain signalling ( Sgherza et al, 2002 ; Hughes and Patterson, 2020 ; Hughes et al, 2021 ). Specifically, plasma concentrations of an opioid neuropeptide known as beta-endorphin (BE) and the endocannabinoid endogenous ligand agonist 2-arachidonoylglycerol (2-AG) have recently been shown to be elevated following BFR exercise in humans ( Hughes and Patterson, 2020 ; Hughes et al, 2021 ). Although there is a distinction between BFR and IPC, the similarities between these techniques involves overlapping mechanisms ( Jessee et al, 2018 ; Patterson et al, 2019 ), which may implicate the involvement of these substances in the IPC response.…”
Section: Effect Of Ipc On Neurological and Perceptual Responses To Ex...mentioning
confidence: 99%
“…Research models have identified several possible mechanisms to explain EIH, like conditioned pain modulation, recruitment of high threshold motor units, a link between baroreceptors and pain pathways, and ischemic and metabolite‐induced pain, which are thought to trigger descending inhibitory pathways 10,16 . Recently, first evidence for the underlying mechanisms of EIH with BFR resistance training hint at the endogenous opioid and endocannabinoid systems and conditioned pain modulation associated with the augmented physiological stress of BFR training 10,37 …”
Section: Discussionmentioning
confidence: 99%
“…Whilst traditional resistance training utilises heavy training loads of 70% or more of 1 repetition maximum (1-RM), low intensity BFRT typically uses loads in the range of 20-40% of 1RM, which may be more tolerable for patients not able to tolerate high muscle-tendon training loads, while still preventing muscle atrophy and promoting hypertrophy [11,133,134]. Additionally, BFRT has been shown to cause exercise-induced hypoalgesia through endogenous opioid and endocannabinoid mechanisms, so could therefore be a useful pain management tool in early musculoskeletal rehabilitation, particularly in the presence of an acute pain response [135][136][137][138].…”
Section: Bfrt Musculoskeletal Rehabilitation Outcomesmentioning
confidence: 99%